Teinver SA and Others v. Argentine Republic. Issue 1 (6th February 2018) - Collins, Anne
Abstract : On 21 July 2017, an International Centre for Settlement of Investment Disputes (ICSID) tribunal (Tribunal) chaired by Judge Thomas Buergenthal, with co-arbitrators Henri C. Alvarez (Claimants' appointee) and Kamal Hossain (Respondent's appointee), issued its award in Teinver SA and others v. Argentine Republic (Award). The Tribunal upheld, by a majority, several of Claimants' claims, and ordered Argentina to pay US320 million in compensation, as well as 20% of Claimants' legal costs and expenses. On 22 November 2017, Argentina registered a request to have the Award annulled.